PEMBUATAN BATU BATA TANPA BAKAR DENGAN CAMPURAN SODIUM HIROKSIDA (NaOH) DAN SODIUM SILIKAT (Na2SiO3 ) - Witjaksana, Budi; Sarya, Gede; Widhiarto, Herry (JHP17 (Jurnal Hasil Penelitian), 2016)
The use of brick is widely used for civil engineering applications such as wallsin residential buildings, buildings, fences, drains and foundations. Bricks in theconstruction of buildings generally have a function as a non-structuralmaterial, in addition to functioning as structural. In this research, the processof making bricks without combustion by utilizing alkaline compound thatfunctions as an adhesive consisting of a solution of Sodium Hydroxide (NaOH)and Sodium Hydroxide (NaOH). The size bricks will be made to have thedimensions of length 230 mm, width 110 mm and thickness 50 mm inaccordance with SNI 15-2094-2000, the Red Brick Wall Couples solid.Keywords: Bricks without combustion, Sodium Hydroxide (NaOH), SodiumHydroxide (NaOH)